The Yeast Heterochromatin Protein Sir3 Experienced Functional Changes in the AAA+ Domain After Gene Duplication and Subfunctionalization. Issue 2 (21st August 2017) - Hanner, Ashleigh S; Rusche, Laura N
Abstract: A key unresolved issue in molecular evolution is how paralogs diverge after gene duplication. For multifunctional genes, duplication is often followed by subfunctionalization. Subsequently, new or optimized molecular properties may evolve once the protein is no longer constrained to achieve multiple functions. A potential example of this process is the evolution of the yeast heterochromatin protein Sir3, which arose by duplication from the conserved DNA replication protein Orc1 . We previously found that Sir3 subfunctionalized after duplication. In this study, we investigated whether Sir3 evolved new or optimized properties after subfunctionalization . This possibility is supported by our observation that nonduplicated Orc1 /Sir3 proteins from three species were unable to complement a sir3 Δ mutation in Saccharomyces cerevisiae . To identify regions of Sir3 that may have evolved new properties, we created chimeric proteins of ScSir3 and nonduplicated Orc1 from Kluyveromyces lactis . We identified the AAA+ base subdomain of KlOrc1 as insufficient for heterochromatin formation in S. cerevisiae . In Orc1, this subdomain is intimately associated with other ORC subunits, enabling ATP hydrolysis. In Sir3, this subdomain binds Sir4 and perhaps nucleosomes. Our data are inconsistent with the insufficiency of KlOrc1 resulting from its ATPase activity or an inability to bind ScSir4 . Thus, once Sir3 was no longer constrained to assemble into the ORC complex, its heterochromatin-forming potential evolved through changes in the AAA+ base subdomain.